Teratoid Cyst with Nephrogenic Elements: A Rare Case - Rijhsinghani, Archana N (Annals of Pathology and Laboratory Medicine, 2020)
Teratoid cyst is a type of dermoid cyst, the lining of which varies from stratified squamous to a ciliated respiratory epithelium containing derivatives of ectoderm, mesoderm and endoderm. The most common location of this cyst is oral cavity and presence of nephrogenic elements has been very rarely reported. We report a very uncommon rare case of teratoid cyst with nephrogenic elements in cyst wall and intestinal duplication cyst in a 6-month-old-female child.